2. CYBER VULNERABILITY MITIGATION IN WI-FI NETWORKS: INTEGRATION OF PENETRATION TESTING, SOCIAL ENGINEERING, AND SECURITY AWARENESS IN XYZ EDUCATIONAL INSTITUTION - Firmansyah; Muhammad Fahrurozi; Rezha Fauzi Ramadhan; Kurniawan; Suroso; Dwikatama (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to empirically and comprehensively assess security vulnerabilitiesin military Wi-Fi networks at the XYZ defense educational institution, encompassing technicalaspects (penetration testing with Aircrack-ng, WPA2 encryption analysis) and human factors(social engineering, personnel security awareness). A convergent mixed-methods approachwas used to integrate quantitative and qualitative data. Penetration testing conducted at fourstrategic locations revealed that 75 percent of the network could be breached in less than 130minutes due to weak passwords with low entropy (less than 60 bits) and default configurations.Meanwhile, a survey of 50 personnel showed that 80 percent were unable to accurately identifyphishing attacks before training, and 65 percent were vulnerable to pretexting scenarios.Vulnerability analysis using the CIA Triad framework revealed violations of Confidentiality (40percent of traffic could be intercepted within 30m), Integrity (20 percent of the network wasvulnerable to Man-in-the-Middle), and Availability (DoS through deauthentication closed 80percent of active sessions). hese findings indicate that the human factor is the biggestvulnerability (95 percent of global cyber breaches originate from human error or manipulation).Therefore, mitigation recommendations are integrative and multi-layered, encompassingtechnical interventions (migration to WPA3 with SAE, implementation of RADIUS and SnortIDS), behavioral interventions (regular awareness training and monthly phishing simulations),and organizational interventions (establishment of a 24/7 CSOC). This integrated frameworkis estimated to reduce attack success by 70 percent, which is crucial for creating military cyberresilience in accordance with the spirit of Sishankamrata and Permenhan No. 82/2014concerning Cyber Defense.